1998
DOI: 10.1080/00380768.1998.10414426
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of soil algae in salinized irrigation land in the arid region of Central Asia

Abstract: Distribution patterns of soil algae were investigated in a 14-year-old farm and its surroundings in the salinized irrigation land of Central Asia. Using a culture dilution method, the densities of five groups of soil algae, green colony group (composed of chlorophytes together with xanthophytes), Chroococcales, Oscillatoriales, Nostocales in the orders of blue-green algae, and diatoms, were estimated. The differences in the distribution patterns among the green colony group, the Oscillatoriales and the N ostoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Salinity later rose to 0.75 to 0.9 g/L and by 2000 was 1.1 to 1.2 g/L [105]. Fertility declined as a consequence, as humus was flushed away and the soil became increasingly saline and alkaline [124] and began to support an altered microflora [125,126]. This has led to diminishing rice yields that remain consistently below the 7 tons/ha predicted by the area's climate [105].…”
Section: Irrigation Areas In the Lower Ili River Basinmentioning
confidence: 99%
“…Salinity later rose to 0.75 to 0.9 g/L and by 2000 was 1.1 to 1.2 g/L [105]. Fertility declined as a consequence, as humus was flushed away and the soil became increasingly saline and alkaline [124] and began to support an altered microflora [125,126]. This has led to diminishing rice yields that remain consistently below the 7 tons/ha predicted by the area's climate [105].…”
Section: Irrigation Areas In the Lower Ili River Basinmentioning
confidence: 99%
“…Cyanobacteria are photosynthetic bacteria that play an important role when subjected to environmental stress. Biological soil crusts with Cyanobacteria can be isolated in many desert systems [ 78 , 90 ]. After years of sand fixation with straw checkerboards combined with different shrubs, it was found that the abundance of Cyanobacteria was higher in the combination containing one leguminous and one nonleguminous shrub (CaKCaM) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The algal strain (BAKg15) was isolated by Tsujimura (1998) from the soil samples collected in a Bakbakty farm located in the Ili River basin, Kazakhstan. The moisture content and pH of the soil sample were 20.2% and 9.1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the green isolates showed characteristics similar to the species reported in the previous taxonomic studies; however, the characteristics of certain isolates were not congruent with the descriptions hitherto made. Tsujimura (1998) found a coccoid green alga (BAKg15) that had two flagella of considerably unequal lengths.…”
mentioning
confidence: 99%